Artistic expressions in architectural buildings in Nairobi - Robinson Onyango, Manguro (2008)
Architecture is both an art and a science. There has been the old age theoretical question as to which one comes first: form or function. The science is recognisable in technological and functional aspects addressed in architecture but the artistic part expressed by the form is hardly recognisable in modern buildings. While we all agree that the artistic expression make architecture interesting, many of the modern day buildings have little regard for artistic expression. The design process has an effect on the resulting design and determines whether the function or form is highly regarded. There are some buildings that define the Nairobi city landscape and have an artistic expression and theory behind their design. This paper examines some of these architectural pieces and analyses their functional aspects as well as resulting artistic expressions. There is an analysis of the process involved in the development of the design of these buildings. It aims at pointing out the strong artistic expressions brought out by these masterpieces and reasons why they stand out amongst others. The design method employed by Architects in developing countries therefore needs to result in functional buildings as well as give the artistic feel that is lacking in many modern day designs that made architecture very interesting in ancient days.